2013
DOI: 10.1074/jbc.m112.392878
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of K339T Substitution Identified in the PB2 Subunit Cap-binding Pocket of Influenza A Virus

Abstract: Background: Amino acid changes in PB2 are associated with evolution of influenza virus. Results: K339T substitution in PB2 cap reduces the cap binding affinity, polymerase activity, RNA synthesis activity, and murine mortality. Conclusion: Substitution in PB2 cap modulates the polymerase activity and virulence by regulating the cap binding activity. Significance: We identified and characterized an emerging K339T substitution in PB2 cap .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…When PB2cap binding interactions are placed in the context of the full-length viral polymerase assembly, the interactions with the β-phosphate will be visible with more clarity. Like 5EG8, the sidechain of His432 assumes two conformations (Figures 1a and 2), whereas the sidechain of Asn429 assumes only one conformation when bound to m 7 GTP, like the single conformation observed in 4ENF (Figures 1b and 2) [10,11]. Lastly, it was observed that sidechains of Phe404, Met431, and Gln406 form a hydrophobic pocket to accommodate the methyl group at position 7 of the cap (Figure 2).…”
Section: Structure Of Mutant Pb2cap From A/california/07/2009 (H1n1) mentioning
confidence: 85%
See 4 more Smart Citations
“…When PB2cap binding interactions are placed in the context of the full-length viral polymerase assembly, the interactions with the β-phosphate will be visible with more clarity. Like 5EG8, the sidechain of His432 assumes two conformations (Figures 1a and 2), whereas the sidechain of Asn429 assumes only one conformation when bound to m 7 GTP, like the single conformation observed in 4ENF (Figures 1b and 2) [10,11]. Lastly, it was observed that sidechains of Phe404, Met431, and Gln406 form a hydrophobic pocket to accommodate the methyl group at position 7 of the cap (Figure 2).…”
Section: Structure Of Mutant Pb2cap From A/california/07/2009 (H1n1) mentioning
confidence: 85%
“…In addition, interactions with α, β, and γ-phosphates in the cap are different in 4CB4 versus 5EG7. Comparisons between 5EG7 and PB2cap from A/Hong Kong/1/68 (H3N2) bound to m 7 GTP (PDB code: 4EQK) [11] revealed similar interactions with the cap, except the side chain of Phe323 is shifted in 4EQK, reducing T-shaped interactions with the guanine moiety (Figure 3b,g) [10].…”
Section: Structural Comparisons Between 5eg7 and Other Structuresmentioning
confidence: 99%
See 3 more Smart Citations